2011
DOI: 10.1007/s13157-011-0154-y
|View full text |Cite
|
Sign up to set email alerts
|

Managed Flood Effects on Beaver Pond Habitat in a Desert Riverine Ecosystem, Bill Williams River, Arizona USA

Abstract: The ecological effects of beaver in warm-desert streams are poorly documented, but potentially significant. For example, stream water and sediment budgets may be affected by increased evaporative losses and sediment retention in beaver ponds. We measured physical attributes of beaver pond and adjacent lotic habitats on a regulated Sonoran Desert stream, the Bill Williams River, after ≥11 flood-free months in Spring 2007 and Spring 2008. Neither a predicted warming of surface water as it passed through a pond n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 47 publications
0
14
0
1
Order By: Relevance
“…Water temperatures in a south‐east Oregon stream were consistently slightly warmer within beaver ponds than in neighbouring unimpounded reaches (Talabere, ), but in the cool tailwaters below Alamo Dam on the Bill Williams River (AZ), Andersen et al . () found no consistent trend in water temperature within beaver ponds. It is interesting that both Lowry () and Pollock et al .…”
Section: Abiotic Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Water temperatures in a south‐east Oregon stream were consistently slightly warmer within beaver ponds than in neighbouring unimpounded reaches (Talabere, ), but in the cool tailwaters below Alamo Dam on the Bill Williams River (AZ), Andersen et al . () found no consistent trend in water temperature within beaver ponds. It is interesting that both Lowry () and Pollock et al .…”
Section: Abiotic Effectsmentioning
confidence: 99%
“…Studies monitoring beaver reintroductions in drylands have reported that beaver ponds maintained perennial standing water (see 'Geomorphology' above), but no data are available to evaluate downstream effects on discharge. In addition, construction of beaver ponds may affect stream water budgets by changing evaporative processes (Andersen et al, 2011). Research is needed to quantify the relationships between beaver dams and hydrologic processes in dryland streams.…”
Section: Hydrologymentioning
confidence: 99%
See 1 more Smart Citation
“…Floods can damage or destroy beaver dams (Andersen & Shafroth, 2010), so larger flood magnitudes on monsoon rivers and in the northwestern United States also may reduce beaver abundance. Changes in beaver populations in turn could affect local and downstream communities, as beavers are formidable herbivores and beaver dams increase lentic habitat and reduce sediment flux (Andersen et al, 2011).…”
Section: Published 2011mentioning
confidence: 99%
“…flow duration, rate of increase to maximum discharge, maximum discharge rate) relate to beaver dam failure. Currently, our ability to make specific management recommendations for instituting flow events in systems with beaver populations is limited, indicating that further work is needed to understand the impact of experimental flood events on beaver dam failure Andersen et al 2011).…”
Section: Pre-experimental Floodmentioning
confidence: 99%